Synthesis and Thermo-chemical Profile of [Pt(NH3)4]C2O4 and [Pt(NH3)4](OOCCH2COO) as New Precursors for Supported Platinum Catalysts - Yu, Juan; Lei, Jing; Yan, Caixian; Jiang, Jing; Ye, Qingsong; Chang, Qiaowen; Liu, Weiping; Chen, Jialin (Asian Journal of Chemistry, 2014)
Two water-soluble complexes featuring [Pt(NH3)4]2+ as a cation and common dicarboxylate (oxalate or malonate) as counter anion have been synthesized, characterized and evaluated for their thermo-chemical profile. The complexes can be easily synthesized in a yield of about 85 % from K2PtCl4 via a series of ligand substitution reactions at mild temperatures and under normal pressures. The thermolysis temperatures and products both in inert and oxidative atmosphere were determined by TG-DTA along with GC-MS. The thermolysis of [Pt(NH3)4](C2O4) begins at about 220 ºC and ends at 270 ºC, forming metallic platinum, CO2 and NH3, whereas [Pt(NH3)4](OOCCH2COO) undergoes a two-phase thermolysis. The first phase corresponds to the loss of one amminia from 105 ºC, followed by the second phase, leading to complete destruction of the complex at 270 ºC. The final products are metallic platinum, CO2, NH3 and CH3CONH2. The thermolysis is caused by the intramolecular redox reaction. These unique properties render the two complexes potential as the new alternative precursors for supported platinum catalysts.